Caregivers' perceptions of compulsory treatment of physical illness in involuntarily psychiatric hospitalization. (May 2023) - Joury, Sophie; Asman, Oren; Gold, Azgad
Background: Physical morbidity is rife among patients with serious mental illness. When they are involuntarily hospitalized and even treated, they may still refuse treatment for physical illness leading clinicians to wonder about the ethics of coercing such treatments. Research aim: This survey study explored psychiatric caregivers' perceptions on whether compulsory treatment of physical illness is legal and whether it is justifiable in patients with serious mental illness and under what circumstances. Research design: A questionnaire that included two case vignettes of an involuntarily hospitalized psychiatric patient with diabetes refusing treatment with insulin for various reasons. The cases differed in terms of diabetes severity. Participants answered questions regarding the appropriateness of involuntary treatment. Participants and research context: Psychiatric medical doctors and nurses working in a mental health center. ( N = 89, 50 female, ages 26–66). Ethical considerations: The study was approved by the Medical Centre Institutional Review Board (IRB) and the University Ethics Committee. The respondents' anonymity was kept. Participation was voluntary and consent was obtained. Results: The severity of the patient's medical condition and their reason for refusing treatment were associated with participants' willingness to give insulin despite patient objection [( F (1, 87) = 49.41, p < .01; ( F (1, 87) = 33.44, p < .01), respectively]. Participants were more inclined to support compulsory treatment if the patient's refusal was "illness-oriented" (i.e. directly related to psychiatric illness). Participants presented diverse views regarding the perceived legality of compulsory treatment of physical illness in such situations (illegal 63.09%; legal 23.8%; 13% unsure). The majority (53.5%–55.3%) of those who thought it was illegal supported compulsory treatment in high-severity, illness-oriented refusal situations. Conclusions: The severity of the medical condition and the reason for treatment refusal influence psychiatric caregivers' willingness to provide compulsory treatment for physical illness in involuntary hospitalized psychiatric patients. Beyond the legal framework, ethical guidelines for these situations are warranted, while decisions should be made on a case-by-case basis.